Iterative Reconstruction Designed for Brain CT: A Correlative Study With Filtered Back Projection for the Diagnosis of Acute Ischemic Stroke. Issue 6 (November 2017) - Iyama, Yuji; Nakaura, Takeshi; Oda, Seitaro; Kidoh, Masafumi; Utsunomiya, Daisuke; Yoshida, Morikatsu; Yuki, Hideaki; Hirata, Kenichiro; Funama, Yoshinori; Harada, Kazunori; Awai, Kazuo; Hirai, Toshinori; et al.
Abstract : Objectives: The objective of this study is to evaluate the usefulness of iterative model reconstruction designed for brain computed tomography (CT) (IMR-Neuro) for the diagnosis of acute ischemic stroke. Methods: This retrospective study included 20 patients with acute middle cerebral artery infarction who have undergone brain CT and 20 nonstroke patients (control). We reconstructed axial images with filtered back projection (FBP) and IMR-Neuro (slice thickness, 1 and 5 mm). We compared the CT number of the infarcted area, the image noise, contrast, and the contrast to noise ratio of the infarcted and the noninfarcted areas between the different reconstruction methods. We compared the performance of 10 radiologists in the detection of parenchymal hypoattenuation between 2 techniques using the receiver operating characteristic (ROC) techniques with the jackknife method. Results: The image noise was significantly lower with IMR-Neuro [5 mm: 2.5 Hounsfield units (HU) ± 0.5, 1 mm: 3.9 HU ± 0.5] than with FBP (5 mm: 4.9 HU ± 0.5, 1 mm: 10.1 HU ± 1.4) ( P < 0.01). The contrast to noise ratio was significantly greater with IMR-Neuro (5 mm: 2.6 ± 2.1, 1 mm: 1.6 ± 1.3) than with FBP (5 mm: 1.2 ± 1.0; 1 mm: 0.6 ± 0.5) ( P < 0.01). The value of the average area under the receiver operating curve was significantly higher with IMR-Neuro than FBP (5 mm: 0.79 vs 0.74, P = 0.04; 1 mm: 0.76 vs 0.69, P = 0.04). Conclusions: Compared with FBP, IMR-Neuro improves the image quality and the performance for the detection of parenchymal hypoattenuation with acute ischemic stroke.